(Nn(B.(Na(B.(NrIMSKIJ(B-(NkORSAKOWs (NMONOGRAFIQs - (Na(B.(NsOLOWCOWs; (Nm(B.(NwOLKOWAs (NREDAKTORs ((NmOSKWAs (NmUZYKAs, 1984)
(NkNIGA POSWQ]ENA VIZNI I TWOR^ESTWU RUSSKOGO KOMPOZITORA(B-(NKLASSIKA(B.s
Keywords: (NMONOGRAFIQs